Variational Transition-State Theory with Optimized Orientation of the Dividing Surface and Semiclassical Tunneling Calculations for Deuterium and Muonium Kinetic Isotope Effects in the Free Radical Association Reaction H + C2H4 → C2H5 - Villà, Jordi; Corchado, José C; González-Lafont, Angels; Lluch, José M; Truhlar, Donald G (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 1999)
We have used canonical variational transition-state theory with multidimensional tunneling contributions (CVT/MT) to calculate 21 kinetic isotope effects (KIE) for the addition of hydrogen atom to ethylene. The potential energies are obtained by variable scaling of external correlation (VSEC). The reorientation of the dividing surface (RODS) algorithm is employed so that the same reaction path can be used for every isotopic substitution. The results show the importance of the tunneling effect for explaining the trends in the KIEs in this almost barrierless reaction. We have predicted the regioselectivity for three different isotopically substituted substrates and have shown how the addition to the most substituted carbon is kinetically favored, especially at low temperature. However, our calculations show no cis/trans selectivity for the isotopically substituted ethylene substrate.